Delay prediction of re-establishing smart permanent virtual circuits in ATM networks [microfilm] - Chin, Yeow Liang (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2002